Minat Mahasiswa Fakultas Ilmu Tarbiyah Dan Keguruan Terhadap Bahasa Arab - Na’im, Tsalisa Miftah Nur (Maliki Interdisciplinary Journal, 2025)
Arabic is an essential language, particularly within the context of Islamic education in Indonesia. However, students’ interest in this language varies and is influenced by multiple factors such as personal motivation, educational background, teaching quality, and academic environment. This study employs a descriptive qualitative approach with data collected through observation, interviews, and questionnaires. The results indicate that students’ interest in Arabic is generally moderate, with some showing high enthusiasm. Innovative and adaptive learning strategies are needed to enhance their motivation.